Midlife crisis : the feminist origins of a chauvinist cliché - Schmidt, Susanne (The University of Chicago Press, 2020)
Introduction -- Double standard -- Feminist origins -- Serious sensation -- Psychology and the crisis of masculinity -- Feminist riposte -- Feminist legacy